2022
DOI: 10.1002/ptr.7478
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoside: A review on its sources, biological activities, and molecular mechanisms

Abstract: Hyperoside is a natural flavonol glycoside in various plants, such as Crataegus pinnatifida Bge, Forsythia suspensa, and Cuscuta chinensis Lam. Medical research has found that hyperoside possesses a broad spectrum of biological activities, including anticancer, anti‐inflammatory, antibacterial, antiviral, antidepressant, and organ protective effects. These pharmacological properties lay the foundation for its use in treating multiple diseases, such as sepsis, arthritis, colitis, diabetic nephropathy, myocardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 87 publications
0
54
0
Order By: Relevance
“…Among them, further investigation is required to evaluate the role of Hyp as an active constituents of Artemisia capillaris —a well-known herbal plant frequently used for treating liver disease [ 104 ]. In addition, based on above medicinal plants containing Hyp, further studies on efficient and economic extraction methods maximizing the purity and yield are needed [ 14 , 95 ]. Hence, Hyp may be an active compound present in various herbal plants that can be widely applied in clinical settings owing to its hepatoprotective, antiviral, antisteatotic, anti-inflammatory, antifibrotic, and anticancer activities.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Among them, further investigation is required to evaluate the role of Hyp as an active constituents of Artemisia capillaris —a well-known herbal plant frequently used for treating liver disease [ 104 ]. In addition, based on above medicinal plants containing Hyp, further studies on efficient and economic extraction methods maximizing the purity and yield are needed [ 14 , 95 ]. Hence, Hyp may be an active compound present in various herbal plants that can be widely applied in clinical settings owing to its hepatoprotective, antiviral, antisteatotic, anti-inflammatory, antifibrotic, and anticancer activities.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the genera Hypericum , Arbutus , Abelmoschus , Zanthoxylum , Houttuynia , etc. are rich in Hyp, and it has been extracted from over 30 herbal plants [ 14 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Phytochemistry Of Hyperosidementioning
confidence: 99%
See 3 more Smart Citations